HEALTH FINANCING STRATEGY AND INNOVATION IN HEALTH INSURANCE IN THE DIGITAL TECHNOLOGY ERA - Rahmayanti; Iswahyudi (PT. Radja Intercontinental Publishing, 2024)
This research aims to describe Health Financing Strategies and Innovations in Health Insurance in the Digital Technology Era. This type of Systematic Literature Review (SLR) method was used to compile this scientific article. Method The approach used in this research is the empirical juridical method. Data analysis was carried out qualitatively, comprehensively and completely. Data analysis means describing the data in a quality manner in sentences that are orderly, coherent, logical, non-overlapping and effective, making it easier to interpret the data and understand the results of the analysis. The research results talk about the potential of health insurance in the digital era, this offers great opportunities in the future. Because insurance is about people, the focus is on financial management of individuals, families and even companies. Apart from saving and investing, insurance is also important. In the era of digitalization, it is increasingly easier for health insurance companies to continue to encourage innovation by collaborating with various stakeholders and certain organizations. There are three forms of digital insurance industry. namely InsurTech Aggregator/Marketplace Aggregator. This is a contact point where we can gather information about the various insurance products of each company. The obstacle in the practice of digital health insurance is that it has not been regulated in special regulations, so it uses conventional health insurance regulations, namely OJK Regulation Number 67/POJK.05/2016 concerning Insurance Licensing and in general it is regulated in OJK Regulation Number 13/POJK.02/2018 concerning Digital Financial Innovation. The application period regarding the regulatory sandbox trial is in accordance with Article 4 of OJK Regulation Number 13/POJK.02/2018 which should be mandatory for all fintech companies but in this case no insurance company has carried out the trial.